The gatekeeper's dilemma: Expert testimony, scientific knowledge and judicial reasoning - Edoardo Peruzzi; Gustavo Cevolani (Duke University, Center for the History of Political Economy (CHOPE), 2024)
We examine the relationship between scientific knowledge and the legal system with a focus on the exclusion of expert testimony from trial as ruled by the Daubert standard in the US. We introduce a simple framework to understand and assess the role of judges as 'gatekeepers', monitoring the admission of science in the courtroom. We show how judges face a crucial choice, namely, whether to limit Daubert assessment to the abstract reliability of the methods used by the expert witness or also to check whether the application of those methods was correct. Undesirable outcomes result from both choices, thereby giving rise to the 'gatekeeper's dilemma.' We illustrate the dilemma by analyzing in some detail two well-known cases of Daubert challenges to economic experts. Finally, we present reasons for the absence of straightforward solutions to the dilemma and for its likely endurance.
Keywords: B40; B41; K40; K41; 330; Expert Testimony; Daubert; Reliability; Scientific Expertise